Bahiranga Yoga: Individual Evolution for Global Harmony: Achieving Balance and Fulfillment in an Industrialized World (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ever since the dawn of Industrial revolution the placid, multidimensional life of human being has given way to a frantic, monotonous and unidimensional lifestyle. Money and material possessions have become the yardstick of success. Progress in every sphere is directed towards the enhancement of the Charvaka value ethics. We need to put a pause on our pace and introspect, rethink and realign individual values with global concerns. The bhairanga yoga which is the first half of the Astanga Marg of Yoga is a journey within encompassing the ethical, physical and psychological dimensions joining each with one’s inner core. Other sutras help in developing deep meaningful relationships with others. It is this inner transformation that will lead to outer effectiveness. We can combine the ageless, ancient wisdom of the past with the vibrant technology of today to build a future where every human being is equipped with the possibility of exploring one’s potential to the fullest with mutual respect for each other and in harmony with nature resulting in the wellbeing of the entire planet.